Interaction between physical and psychosocial work risk factors for low back symptoms : a study of prevalence, risk factors, and interaction between physical and psychosocial work risk factors for low back symptoms and its consequences (reduced activities and absenteeism) in a random sample of workers in New Zealand and in Indonesian coal mining workers : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Ergonomics at Massey University, Manawatu, New Zealand - Widanarko, Baiduri (Massey University, 2013)
The prevalence of low back symptoms (LBS) in developed and industrially developing countries (IDCs) is high, and there have only been a few studies in New Zealand and IDCs. It is well known that the risk factors for LBS include physical and psychosocial exposures, but the interaction between these is not well understood. Even less is known about prevalence of, and risk factors for, twopossible consequences of LBS (reduced activities and absenteeism). Hence, this thesis examines the prevalence, risk factors, and the interaction between physical and psychosocial work risk factors for LBS and its consequences in a developed country and an IDC. This was done in two cross-sectional studies of: A) a large random sample of workers in New Zealand, and; B) Indonesian coal mining workers. In telephone interviews of 3,003 participants (1,431 males and 1,572 females) aged 20-64 randomly selected from the New Zealand Electoral Roll, the 12-month period prevalence of LBS, reduced activities, and absenteeism due to LBS were 54%, 18%, and 9%, respectively. Risk factors of LBS for the whole population (males and females) increased with work in awkward or tiring positions and stressful jobs. Awkward or tiring positions at work, dissatisfaction with contact and cooperation with management, and stressful jobs were risk factors for women but not for men. The only risk factor for reduced activities was lifting. Risk factors for absenteeism were working in awkward or tiring positions and in a cold or damp environment. In a self-administered questionnaire among 1,294 Indonesian coal mining workers (1,252 males and 42 females), the 12-month period prevalence of LBS, reduced activities, and absenteeism due to LBS were 75%, 16%, and 13%, respectively. This study afforded an opportunity to examine selection bias due to a healthy worker effect. It showed that blue-collar work (as opposed to white-collar work) was a risk factor for LBS, after adjustment for a healthy worker effect and other potential confounders. The presence of LBS and smoking increased the risk of reduced activities and absenteeism. This study also indicated that those who were exposed to both high physical (awkward posture, whole-body vibration, using vibrating hand tools, and lifting) and high psychosocial (high effort, low reward, job dissatisfaction, and work stress) factors were most likely to report LBS and both consequences. High psychosocial exposure increased the likelihood of reporting LBS, but high physical exposure did so for reduced activities and absenteeism. Current smokers were more likely to report LBS consequences than nonsmokers. Permanent employment and night shift work increased the risk of LBS and its consequences. There was an interaction between physical and psychosocial exposures for LBS. The overall risk for LBS was greater than the sum of the individual risks due to physical and psychosocial factors (as indicated by departure from an additive model of risk). Thirty-nine percent of LBS cases among those who were exposed to high physical and high psychosocial risk factors were due to exposure to both factors. There were also interactions between the risk factors for reduced activities due to LBS, although not significant, whereas for absenteeism due to LBS it was not present. The implications of these findings for New Zealand workers are that LBS and its consequences could be reduced by using interventions designed to avoid or minimise exposure to physical and psychosocial work factors. In addition, environmental factors should also be improved in order to reduce the consequences of LBS. For Indonesian coal mining workers, addressing both physical and psychosocial factors in the workplace is likely to reduce up to 39% of LBS cases among workers exposed to both factors. This will in turn, reduce the risk of LBS consequences. The intervention strategy should also focus on permanent employment, night shift work, and smokers.
Chapter 2 published as: Widanarko, B., Legg, S., Stevenson, M., Devereux, J., Eng, A., Mannetje, A., Cheng, S., Douwes, J., Ellison-Loschmann, L., McLean, D., & Pearce, N. (2011). Prevalence of musculoskeletal symptoms in relation to gender, age, and occupational/industrial group. International Journal of Industrial Ergonomics, 41(5), 561-571. To link to this article: http://dx.doi.org/10.1016/j.ergon.2011.06.002. Chapter 3 published as: Widanarko, B., Legg, S., Stevenson, M., Devereux, J., Eng, A. Mannetje, A., Cheng, S., & Pearce, N. (2012). Gender differences in work-related risk factors associated with low back symptoms. Ergonomics, 55(3), 327-342. To link to this article: http://dx.doi.org/10.1080/00140139.2011.642410. Chapter 4 published as: Widanarko, B., Legg, S., Stevenson, M., Devereux, J., Eng, A., Mannetje, A., Cheng, S., & Pearce, N. (2012). Title:Prevalence and work-related risk factors for reduced activities and absenteeism due to low back symptoms. Applied Ergonomics, 43(4), 727-737. To link to this article: http://dx.doi.org/10.1016/j.apergo.2011.11.004. Chapter 5 published as: Widanarko, B., Legg, S., Stevenson, M., Devereux, J., & Jones, G. Prevalence of low back symptoms and its consequences in relation to occupational group. American Journal of Industrial Medicine, 56(5), 576-589. To link to this article: http://dx.doi.org/10.1002/ajim.22116. The definitive version is available at www3.interscience.wiley.com
Keywords: Backache; Lower back pain; Epidemiology; Risk factors; Psychological aspects; Occupational diseases; Industrial safety; Coal miners; New Zealand; Indonesia